2013
DOI: 10.5740/jaoacint.11-257
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC Method for Simultaneous Analysis of Stevioside and Rebaudioside-A in Stevia rebaudiana

Abstract: An HPTLC method was developed and validated for simultaneous determination of stevioside (STE) and rebaudioside-A (REB-A) in Stevia rebaudiana leaves. The HPTLC separation was performed on precoated silica gel 60F254 HPTLC plates with the mobile phase ethyl acetate-ethanol-acetone-water (15 + 3 + 6 + 6, v/v/v/v). The densitometric quantification of steviol glycosides was carried out at Amax 580 nm in the reflection-absorption mode after spraying with anisaldehyde-sulfuric acid reagent. Rf values were 0.34 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Several analytical techniques have been used to determine the concentrations of glycosides in S. rebaudiana, including thin layer chromatography (HPTLC) [8]- [10], capillary electrophoresis [11] [12], LC/mass spectrometry [13], electrospray ionization mass spectrometry (ESI-MS) [3], infrared spectroscopy [11] [14], and highperformance liquid chromatography (HPLC) [15]- [20] among others, which vary in sensitivity, precision and accuracy. However, the FAO/WHO Joint Expert Committee on Food Additives (JECFA) in its 73rd meeting has recommended an HPLC method for determination of steviol glycosides [21] and therefore it is the most appropriate to use.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical techniques have been used to determine the concentrations of glycosides in S. rebaudiana, including thin layer chromatography (HPTLC) [8]- [10], capillary electrophoresis [11] [12], LC/mass spectrometry [13], electrospray ionization mass spectrometry (ESI-MS) [3], infrared spectroscopy [11] [14], and highperformance liquid chromatography (HPLC) [15]- [20] among others, which vary in sensitivity, precision and accuracy. However, the FAO/WHO Joint Expert Committee on Food Additives (JECFA) in its 73rd meeting has recommended an HPLC method for determination of steviol glycosides [21] and therefore it is the most appropriate to use.…”
Section: Introductionmentioning
confidence: 99%
“…reported a HPTLC method for the quantification of steviolbioside (99), stevioside (100) and rebaudioside‐A (101) from leaves of S. rebaudiana (Figure ) . Simultaneous HPTLC‐based quantification of stevioside and rebaudioside A, in S. rebaudiana and different stevia samples collected from the Indian subcontinent was also reported .…”
Section: Food and Nutritionmentioning
confidence: 99%
“…A literature survey of the analytical instrumentation used in the food industry revealed that high performance liquid chromatography (Woelwer-Rieck et al, 2010;Zimmermann et al, 2011;Puri et al, 2012), high performance thin layer chromatography (Jaitak et al, 2008;Londhe and Nanaware, 2013), hydrophilic interaction liquid chromatography (Well et al, 2013), liquid chromatographymass spectrometry (Shah et al, 2012;Kakigi et al, 2013), liquid chromatography coupled to electro spray ionization mass spectrometry (Rajasekaran et al, 2008;Montoro et al, 2013) and capillary electrophoretic methods (Bathinapatla et al, 2015a) have been employed for the determination of steviol glycosides, mainly Reb A in different food samples. On the other hand electrochemical methods, in contrast have significant advantages such as faster response time, lower cost, higher sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%